Managing traumatic aortic rupture: a case study - Gierek, Danuta; Włodarczyk, Leszek; Kaczmarska, Adriana; Bachowski, Ryszard; Gryboś, Andrzej; Gierek, Michał (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
This paper describes a case of a 26-year-old victim of a car accident, resulting in a multi-organ injury, including head trauma, thoracic contusion and the descending aorta’s rupture. Thanks to a cardiac surgery performed and many weeks of intensive therapy and rehabilitation, a complete recovery was achieved.